Engaging Italy : American Women's Utopian Visions and Transnational Networks. - Madden, Etta M. (Albany : State University of New York Press, 2022)
Traces literary and social connections among three American women navigating the changing political landscape of 1860s and '70s Italy.
"A Ways and Means Committee" -- Gothic Riffs on Earthly Realities -- Heavenly and Eternal Visions -- Political Visions in "Gossip Abroad" -- Published Documents of the Italo-American Schools -- Private Letters and Their Political Meanings -- Chapter 9 Anne Hampton Brewster: A Catholic Correspondent Negotiates New Rome -- Anxieties of Arrival-Creature Comforts Compromised -- Nero Nardi and the Vatican Council -- The APOSTATE!: Negotiating Roman Catholicism -- Women Loving Women: A Necessary Circle of Admirers -- Brewster's Life Alone: Utopian and Dystopian Visions -- Chapter 10 Caroline Crane Marsh: "The Power of Doing a Great Service" -- Surrogate Motherhood: The Power and Service of Letting Go -- Serving Schools: Fundraising at Home and Abroad -- Transformations of a Reformer and Litterateur -- "In Vain Have I Labored": Ideas of Italian Reform Revised -- Coda: Residual Ripples -- Hidden Lives &amp -- Unvisited Tombs -- Appendix A: "To ____ ____." -- Appendix B: "For Queen Anne" -- List of Abbreviations -- Notes -- Bibliography -- Index.
Description based on publisher supplied metadata and other sources.
JSTOR
Keywords: Women -- Italy -- History -- 19th century; Americans -- Italy -- History -- 19th century; Italy -- Politics and government -- 1849-1870.; Italie -- Politique et gouvernement -- 1849-1870.; Femmes -- Italie -- Histoire -- 19e siècle.; Americans; Politics and government; Women; Italy; 1800-1899; History